Optimal single-embryo mass spectrometry fingerprinting - Tata, Alessandra; Sudano, Mateus J. [UNESP]; Santos, Vanessa G.; Landim-Alvarenga, Fernanda D.C. [UNESP]; Ferreira, Christina R.; Eberlin, Marcos N. (Wiley, 2013)
In pre-implantation embryos, lipids play key roles in determining viability, cryopreservation and implantation properties, but often their analysis is analytically challenging because of the few picograms of analytes present in each of them. Matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS) allows obtaining individual phospholipid profiles of these microscopic organisms. This technique is sensitive enough to enable analysis of individual intact embryos and monitoring the changes in membrane lipid composition in the early stages of development serving as screening method for studies of biology and biotechnologies of reproduction. This article introduces an improved, more comprehensive MALDI-MS lipid fingerprinting approach that considerably increases the lipid information obtained from a single embryo. Using bovine embryos as a biological model, we have also tested optimal sample storage and handling conditions before the MALDI-MS analysis. Improved information at the molecular level is provided by the use of a binary matrix that enables phosphatidylcholines, sphingomyelins, phosphatidylserines, phosphatidylinositols and phosphoethanolamines to be detected via MALDI(±)-MS in both the positive and negative ion modes. An optimal MALDI-MS protocol for lipidomic monitoring of a single intact embryo is therefore reported with potential applications in human and animal reproduction, cell development and stem cell research. Copyright © 2013 John Wiley & Sons, Ltd. Copyright © 2013 John Wiley & Sons, Ltd.
Keywords: binary matrix; embryo; fingerprinting; matrix-assisted laser desorption-mass spectrometry (MALDI-MS); phospholipids; Binary matrix; MALDI-MS; Matrix-assisted laser desorption/ionization mass spectrometry; Membrane lipid composition; Microscopic organisms; Pre-implantation embryos; Optimization; Phospholipids; Stem cells; Mass spectrometry; phosphatidylcholine; phosphatidylinositol; phosphatidylserine; phosphoethanolamine; sphingomyelin; cell maturation; female; fertilization in vitro; lipidomics; mass spectrometry; matrix associated laser desorption ionization mass spectrometry; nonhuman; oocyte; priority journal; reproduction; stem cell; storage